Pengembangan Media Pembelajaran Pendidikan Agama Islam Berbasis Analisis Lectora Inspire - Nurbaiti, Umi Choiriyah (Universitas Hamzanwadi, 2017)
This study aim to describe the process of developing islamic education learning media using Lectora Inspire based on it’s validity and usability. This study was conducted in SMA Negeri 4 Berau. The characteristic of this study is research and development. The model of development that is applied in this research is ASSURE model. This study successfully developing the islamic education learning media using Lectora inspire, spesifically described by, (1) validation as islamic learning media is obtained by: (a) validity score of the content as a learning media is 91% and categorize as very good, (a) validity score from ICT expert as a learning media is 79% and categorize as decent, and (c) validity score from education technology expert is 84% and categorize as decent; (2) usability as the learning media is obtained by: (a) analyzing the result of learning with RPP fulfilled score of 85% and categorize as decent, (b) any obstacle are resolved, (c) response from the student is scored 81% and categorized as positive. Theoretically this study can increase our reference, information and understanding of Islamic education learning method. On the implementation, this study contributes to support student achieving the objective of islamic learning, as well for teachers to carry out the effective teaching and learning process.